2017
DOI: 10.1016/j.tate.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of new technologies: Improving literacy and engaging learners at risk of social exclusion in the UK

Abstract: This paper explores the effectiveness of new technologies in developing literacy within subject disciplines of secondary school students at risk of social exclusion. The research was undertaken as a collaborative project across five schools, including qualified and pre-service teachers in the United Kingdom. This paper provides an overview of the study and presents key findings related to impact on student progression and engagement and impact on teachers. The research indicates the affordances of the software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…This implies that a wider range of leadership support in terms of provision of training in technology is needed for teachers to be able to integrate ICT into their teaching. This result of this study is in line with findings by other researchers (Boulton, 2017;Japhet & Usman, 2018;Shin, 2015). Lastly, this study revealed that competence strongly correlated with self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This implies that a wider range of leadership support in terms of provision of training in technology is needed for teachers to be able to integrate ICT into their teaching. This result of this study is in line with findings by other researchers (Boulton, 2017;Japhet & Usman, 2018;Shin, 2015). Lastly, this study revealed that competence strongly correlated with self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…Leadership engages the acquisition and coordination of these factors within the settings and limitations of the institution in defining and realizing the preferred results. Numerous studies (Boulton, 2017;Japhet & Usman, 2018;Shin, 2015) have found that leadership support is a stronger determinant of teachers' integration of ICT into teaching. Schiller (2003) believes that "without the leadership support, the educational potential of information and communication technology may not be realized" (p. 171).…”
Section: Leadership Supportmentioning
confidence: 99%
“…However, these researches also highlighted the barriers toward the successful integration of the technologies in classrooms. The listed factors include the lack of senior management support, lack of planning, limited access to the technology, school firewall (Hramiak & Boulton, 2013), teachers’ low confidence, resistance to change, lack of time, lack of technical support (Bingimlas, 2009; Murray, Nuttall, & Mitchell, 2008), teachers’ skill attitude and beliefs, students’ skill (Gaffney, 2010), and access to technology (Boulton, 2015; Hammond et al., 2009; Pelgrum & Doornekamp, 2009). The research conducted among Iranian students shows that the lack of necessary rules and regulation and the traditional structure of Iranian schools were the main barriers toward the successful implementation of smart schools (Mahmudi, Nalchigar, & Ebrahimi, 2008; Taleb & Hassanzadeh, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learners in the project are in primary (aged 3-11) or secondary schools (aged [11][12][13][14][15][16][17][18][19]. There are also learners in careers guidance or working in industry but these are not reported in this paper.…”
Section: Introductionmentioning
confidence: 99%